A study to evaluate the relationship between diabetes mellitus and cognitive dysfunction - Rakesh Kumar Patel,; Karan Saran Kapur,; Sardar Eske, (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is the most common endocrine disorder. It leads to slow progressive end-organ damage (both microvascular and macrovascular). The cognitive dysfunction is a less known and less addressed complication of DM. Aims and Objectives: This study aims to evaluate the cognitive dysfunction in the patient with DM and to assess the cognitive dysfunction by Mini-Mental State Examination (MMSE) of the patients who are suffering from DM. Materials and Methods: A total of 979 diabetic patients were screened for cognitive dysfunction using MMSE score. The patients were evaluated as per the history. MMSE is a 30-point questionnaire which is mainly used to measure the cognitive impairment. Results: A total of 979 diabetic patients were included in the study out of which 44.7% of the patients were found to have cognitive dysfunction. Cognitive impairment was more prevalent in female diabetics (51%) as compared to male diabetics (39.8%). The result is significant at P<0.05. Patients with longer duration of diabetes had much higher incidence of cognitive impairment (80.9%) as compare with the patients with short duration of diabetes which has lesser incidence of cognitive impairment (16.2%). P<0.001 was considered statistically significant. Conclusion: Majority of the subjects suffering from DM have concomitant cognitive impairment. There is a significant cognitive impairment seen in subjects with DM. Early recognition and management of the cognitive dysfunction will help in improving quality of life.